Study on the influence factors of urban subway project delay in the initial construction stage. (18th August 2018) - Wang, Wenbao; Lin, Wenhe
Abstract: The factors that lead to the delay of construction project of urban subway construction are complicated. In this paper, the influence factors of urban subway project delay in the initial construction stage was studied and the urban subway project delay evaluation system consisting of 37 key indicators was established by combining with the first-hand data obtained from the subway construction management and related literature. The weight of each indicator in the evaluation system was calculated by using the structural equation model to analyze the data of the questionnaire. The core influencing factors are analyzed and the corresponding suggestions were put forward to minimize the occurrence of delays in subway construction.